Acquiring Scientific Process and Innovative Thinking Skills for Secondary School Sixth Grade Students through Digital Activities: An Action Research - Emine Akkaş Baysal; Ali Osman Yörük; İjlal Ocak (Journal of Science Learning, 2022)
This research aims to develop students' scientific process and innovative thinking skills using digital activities in distance and face-to-face education. A total of 12 sixth-grade students in a primary school participated in the study. The research was action research. The analysis was carried out in the "Transmission of Electricity" unit within the scope of the sixth-grade Science Course in 5 weeks and 20-course hours. The quantitative data were collected with "The scientific Process Skills Scale" and "Innovative Thinking Scale". Semi-structured interview forms, researcher, and student diaries were used to acquire qualitative data. The study's findings revealed that students showed improvement in gaining scientific processes and innovative thinking skills. It was observed that there was a significant difference between the mean scores of the science process skills test applied before and after the application in favor of the post-test. It was determined that students' use of scientific thinking skills increased during the experiments and activities. Moreover, students identified themselves with the work of scientists and improved their skills in conducting scientific processes. This situation shows that students can gain a scientific approach and innovative thinking skills with the active use of digital activities, especially in Science.